Methodology and research on the human resource practices of multinational enterprises in Australia - McDonell, A.; Russell, H.; Burgess, John; Bartram, T. (National Institute of Labour Studies, 2011)
Despite Australia being a major source of foreign direct investment and an important location for multinational enterprises (MNEs), there is a lack of information about the operations of MNEs in Australia, particularly with respect to their human resource management (HRM) practices. This paper examines the existing datasets and research on the HRM practices of MNEs in Australia. One of the main weaknesses with existing quantitative research on the HRM practice of MNEs is the absence of a systematic or representative data set of MNEs. To address this issue, we describe the process that we followed in order to develop a new set that will assist researchers interested in understanding and explaining the HRM practices of the Australian operations of MNEs.